IN VITRO DIGESTIBILITY ANALYSIS OF SHEEP BASED ON CORN COBS FERMENTED WITH WINPROB AT DIFFERENT TIMES - Tiara Adelia; Warisman, Warisman (Bajang Institute, 2024)
The aim of this research was to determine the efficiency of corn cobs fermented with Winprob for different periods of time on dry matter digestibility, organic matter digestibility and crude fiber digestibility in vitro. The hypothesis of this research is that giving Winprob probiotics to fermented corn cobs for different periods of time can increase dry matter digestibility, organic matter digestibility and crude fiber digestibility. The research design used was a non-factorial completely randomized design (CRD) with 4 treatments and 5 replications. The treatments studied were as follows: P0 (control/unfermented corn cobs); P1 (Corn cobs fermented with Winprob for 7 days); P2 (Corn cobs fermented with Winprob for 14 days) and P3 (Corn cobs fermented with Winprob for 21 days). The parameters observed were Dry Matter Digestibility, Organic Matter Digestibility and Crude Fiber Digestibility of sheep in vitro. The results of research on the KcBk and KcSK parameters showed that the treatment had a very significant effect (P<0.01). Meanwhile, the KcBO parameter showed that the treatment had no real effect (P>0.05).